Rapid Prototyping of a Low-cost Graphene-based Impedimetric Biosensor. (2017) - Popescu, Sinziana; Dale, Carl; Keegan, Neil; Ghosh, Biswajit; Kaner, Richard; Hedley, John
Abstract: This paper presents a preliminary investigation towards rapid prototyping of a low-cost biosensor based on reduced graphene oxide (rGO). The devices are fabricated via a laser scribing process and their functionality is demonstrated by their functionalization and subsequent immobilization of 7% bovine serum albumin (BSA). Non-faradaic electrochemical impedance spectroscopy (EIS) indicated a 33-42% decrease in impedance upon immobilization. An electroless nickel deposition process is demonstrated to enable electrical contacts to the device, with optimized plating conditions (pH, temperature) leading to a rGO-nickel contact resistance of 19 Ω/mm 2 .